Clinical and Epidemiological Profiles of Patients Admitted to a Pediatric Cardiac Intensive Care Unit - Guimarães,Juciane Rocha (2020)
Abstract Background: Congenital and acquired heart diseases are important causes of morbidity and mortality in children. In critical congenital heart defects, when treatment is not adequate, clinical manifestations may lead to death in the neonatal period. Objective: To establish the clinical and epidemiological profile of patients admitted to the pediatric cardiac intensive care unit (UTI) in a tertiary hospital. Methods: This was a cross-sectional study conducted from January 2013 to December 2014, based on analysis of patients' medical records. The study sample was composed of 307 children and adolescents with congenial and acquired heart diseases. The score Risk Adjustement for Congenital Heart Surgery 1 (RACHS-1) was used for categorization of the various surgical procedures. Descriptive statistics were calculated using the Satistical Package for Social Sciences (SPSS). Categorical variables were compared using the Pearson's chi-square test, considering a level of significance of 5%. Results: There was a predominance of patients aged between 28 days and one year (44%). Congenital heart diseases (91.9%) prevailed over acquired heart diseases (8.1%). Extracorporeal circulation was used in 138 patients who underwent surgical procedures, lasting from 12 to 261 minutes. Most patients (88.9%) were discharged from the ICU and 11.1% died. Using the score RACHS-1, corrective cardiac surgery was performed in 75.8% and paliative surgery in 24.2% of the patients. Conclusions: Patients aged between 28 days to one year, with cyanotic congenital heart disease, undergoing cardiac surgery with extracorporeal circulation duration longer than 120 minutes are at a higher risk of death.